Muribaculum gordoncarteri sp. nov., an anaerobic bacterium from the faeces of C57BL/6J mice. Issue 8 (20th August 2020) - Miyake, Sou; Ding, Yichen; Soh, Melissa; Low, Adrian; Seedorf, Henning
Abstract : An anaerobic bacterial strain, named TLL-A4 T, was isolated from fecal pellets of conventionally raised C57BL/6J mice. Analysis of the 16S rRNA gene indicated that the strain belongs to the phylum Bacteroidetes and, more specifically, to the recently proposed Muribaculaceae (also known as S24-7 clade or Candidatus Homeothermaceae). Strain TLL-A4 T 's 16S rRNA gene shared 92.8 % sequence identity with the type strain of the only published species of the genus Muribaculum, Muribaculum intestinale DSM 28989 T . Genome-sequencing of TLL-A4 T was performed to compare average amino acid identity (AAI) value and percentage of conserved proteins (POCP) between both strains. The AAI analysis revealed that strain TLL-A4 T had high identity (69.8 %) with M. intestinale DSM 28989 T, while the POCP was 56 %. These values indicate that strain TLL-A4 T could be considered a member of the genus Muribaculum but not belonging to the species M. intestinale . Quinone analysis indicated MK10 (63 %) and MK11 (32 %) as major quinones in the membrane, while MK9 was only present as a minor component (5 %). The main cellular fatty acid was anteiso-C15 : 0 (42.8 %); summed feature 11 (17.5 %), C15 : 0 iso (13.4 %), C18 : 1  ω9 c (5.6 %), C16.0 3-OH (4.5 %) and C15 : 0 (4.2 %) were detected in minor amounts. Analysis of enzyme activities using the API 32A and API 20A kits indicated major differences between strain TLL-A4 T and Muribaculum intestinale DSM 28989 T . Based on genotypic, phylogenetic and phenotypic differences, strain TLL-A4 T is considered to represent a novel species of the genus Muribaculum, for which the name Muribaculum gordoncarteri sp. nov. is proposed. The type strain is TLL-A4 T (=DSM 108194 T =KCTC 15770 T ).